Antidepressants and mortality risk in a dementia cohort: data from SveDem, the Swedish Dementia Registry - Enache, D; Fereshtehnejad, S-M; Kåreholt, I; Cermakova, P; Garcia-Ptacek, S; Johnell, K; Religa, D; Jelic, V; Winblad, B; Ballard, C; Aarsland, D; Fastbom, J; et al. (Acta psychiatrica Scandinavica, 2016)
BACKGROUND: The association between mortality risk and use of antidepressants in people with dementia is unknown. OBJECTIVE: To describe the use of antidepressants in people with different dementia diagnoses and to explore mortality risk associated with use of antidepressants 3 years before a dementia diagnosis. METHODS: Study population included 20 050 memory clinic patients from the Swedish Dementia Registry (SveDem) diagnosed with incident dementia. Data on antidepressants dispensed at the time of dementia diagnosis and during 3-year period before dementia diagnosis were obtained from the Swedish Prescribed Drug Register. Cox regression models were used. RESULTS: During a median follow-up of 2 years from dementia diagnosis, 25.8% of dementia patients died. A quarter (25.0%) of patients were on antidepressants at the time of dementia diagnosis, while 21.6% used antidepressants at some point during a 3-year period before a dementia diagnosis. Use of antidepressant treatment for 3 consecutive years before a dementia diagnosis was associated with a lower mortality risk for all dementia disorders and in Alzheimer's disease. CONCLUSION: Antidepressant treatment is common among patients with dementia. Use of antidepressants during prodromal stages may reduce mortality in dementia and specifically in Alzheimer's disease.
Keywords: Registries; Švédsko; dementia; Humans; demence; lidé středního věku; antidepressant treatment; registrace; Sweden; antidepresiva; Aged; Antidepressive Agents; Female; mortality risk; senioři; lidé; ženské pohlaví; Male; Middle Aged; Aged, 80 and over; Dementia; Alzheimer's disease; senioři nad 80 let; mužské pohlaví; prospektivní studie; Prospective Studies